(untitled) (Bangladesh Journal of Microbiology, 2020)
High prevalence of antibiotic resistance is necessitating the investigation of novel antimicrobials from natural herbs and plant. So, this present study investigated two of indigenously cultivated jute plants, Corchorus capsularis (white jute)and Corchorus olitorius (tossa jute) for their antibacterial activity. Lipophilic extracts of leaves were prepared and fractionated by column chromatography resulting in 6 fractions of the extract of C. olitorius leaves (At, Bt, Ct, Dt, Et and Ft) and 11 fractions in case of white jute leaves (Aw, Bw, Cw, Dw, Ew, Fw, Gw, Hw, Iw, Jw and Kw). Each fraction of both of the leaves extracts were used to tested by agar well diffusion assay against Staphylococcus aureus and Escherichia coli along with a control organism, E. coli DH5±. While the fractions of C. olitorius leaves showed higher antibacterial activity against S. aureus, fractions of the extract of C. capsularis leaves were more effective against E. coli. The At fraction of C. olitorius extract showed the highest inhibition zone of 19 ± 2.80 mm against S. aureus and Dw fraction of C. capsularis extract had the highest inhibition zone of 15 ± 2.3 mm against E. coli (p <0.05). The extract of C. olitorius leaves showed comparatively higher antibacterial effect than that of C. capsularis leaves. Considering the promising finding regarding the antibacterial effectiveness, these fractions of the leave extract should be analyzed further to isolate the exact bioactive component to develop the lead component of new generation antibacterial drugs. Bangladesh J Microbiol, Volume 36 Number 2 December 2019, pp 69-73